The School Readiness in Implementing the Merdeka Curriculum in Pekanbaru : A Survey of Teachers and Students’ Perspectives - Bastian, Adolf; Firdaus, M; Rizky, Ramanda (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2023)
This study aims to assess the school readiness in implementing the Merdeka Curriculum in the Year Â Â 2022/2023 at several SMA/SMK in Pekanbaru City. This study used a descriptive quantitative with a survey metod. Data collection techniques are carried out using questionnaires and observations, with a sample of 32 SMA/SMK selected through a purposive sampling technique. Data analysis techniques using descriptive analysis according to the variables that had been determined. Based on the research results show that the school’s understanding Â of the Merdeka Curriculum was very high, reaching 94%. In total, 81% of SMA / SMK have met the requirements and have been appointed by the Â Indonesian Minister of Education, Culture, Research and Technology (Mendikbudristek) to implement the Merdeka Curriculum. Teachers’ competence in supporting the Merdeka Curriculum reached 75%. In terms of studentsâ€™ participation in effective learning, it is not optimal since it reached only 16%. It is necessary to improve policy and procedural support, around 62% stated this. However, only 56% of schools use learning modules from the Mendikbudristek. Besides, the use of the Minimum Competency Assessment (MCA) and Character Survey also reached 56%, while the use and preparation of Â independence learning lesson plans reached 62%. In conclusion, a number of challenges remain in the implementation of the Merdeka Curriculum in SMA/SMK, especially related to infrastructure, student participation, and policy support, but it has also achieved some level of success in terms of teacher competence and the use of teaching materials.